An indoor based push notification for location-based marketing using bluetooth smart ready technology / Nur Farehah Alias - Alias, Nur Farehah (2017)
Nowadays, location-based marketing is used by companies to advertise their product to their customers through mobile devices. Advertisement can be sent in different ways, such as cellular wireless internet, Global Positioning System (GPS) through push technology. Even though push notification that can be send by using Bluetooth low energy technology which allow user to receive advertisement in their smartphone already exist, but it lack in several aspect such as it does not consider about user preferences such as user difficult to keep their own privacy because the app keeps send notification without consider user’s privacy. Next, location awareness such as user always get irrelevant information in irrelevant place, they also find that it is difficult to get information or content only by manually search for advertising or information. Therefore, this project has proposed a method called token based alert notification. There are three algorithm developed for token based alert notification which is tokenization algorithm, token matching algorithm and item identification algorithm. This algorithm developed to allow user to receive push notification effectively based on the location of user’s smartphone that can be detected by Bluetooth Smart Ready Technology (BLE). Moreover, two experiment have been conducted in order to evaluate the performance of the project and the result have conclude that token based alert notification has performed well in terms of the ability to send push notification alert accurately. Android smartphone is used in order to test this algorithm.